Jaume Plensa. The Four Elements - Symons, Stéphane; Plensa, Jaume; Wagemans, Johan; Derez, Mark; Thys, Erik; Van Imschoot, Tom; Gysen, Rebecca; Landuydt, Karen; Lambrechts, Stéfanie (Leuven University Press, 2024)
Special edition on the first permanent sculpture by Jaume Plensa in Belgian public space. Acclaimed Spanish visual artist, sculptor, designer and engraver Jaume Plensa is renowned for his ability to weave spirituality, corporeality, and collective memory into his sculptures and installations, using a wide range of materials. Many of his iconic sculptures can be found in public spaces, in some of the most evocative places in the world. The city of Leuven now joins this list with the acquisition by KU Leuven of The Four Elements, the first permanent sculpture by Jaume Plensa in Belgian public space. The sculpture The Four Elements consists of two parts in bronze, located in two places, the gallery of the KU Leuven University Library and the newly created St-Raphaël Square. The first part, Fire, commemorates the resurrection of the University Library after the devastating fire of World War I. Water, Earth, Air, the second part, rises like a totem pole on a new urban site that is a meeting point for health care and medicine. This collection of essays documents how the two parts of the sculpture and its two sites represent a broader trinity of interaction and togetherness: between the university and the city and its public spaces, between research and art, between the study of health (in this case the brain) and organizing care.